Artikel Review: Implementasi Sistem Internet of Things (IoT) Pada Industri Perunggasan - Hidayati Soesanto, Iman Rahayu; Wahjuni, Sri; Tanti, Ariyani (Jurnal Ilmu dan Teknologi Peternakan Terpadu, 2024)
The implementation of Internet of Things (IoT) systems in the poultry industry has shown great potential in enhancing poultry efficiency and productivity. IoT technology enables real-time monitoring of various aspects of the coop environment, such as temperature, humidity, air quality, and lighting, as well as the health conditions of the chickens. Through connected sensors and communicating devices, data can be collected and analyzed to optimize the maintenance conditions of the chickens, thereby improving livestock health and reducing mortality rates. Additionally, IoT systems can automate feeding and watering processes, contributing to operational cost and time savings. This article reviews various case studies and research related to the application of IoT in the poultry industry. The review results indicate that the use of IoT not only increases operational efficiency but also aids in faster and more accurate decision-making based on precise data. However, challenges such as high initial costs, the need for adequate technological infrastructure, and specialized expertise in managing IoT systems must be addressed. Therefore, a strategic approach and collaboration among farmers, the government, and technology providers are required to maximize the benefits of IoT in the poultry industry.